Vous êtes sur la page 1sur 4

Algebra TD 2

February 4, 2022

Problem 1.
Given V be vector space of dimension n et f ∈ End(V ). Show that the following assertions are equivalent:

(a) Ker(f ) ⊕ Im(f ) = V



(b) Im(f ) = Im f 2

(c) Ker(f ) = Ker f 2

Problem 2.
Soient f et g deux endomorphismes d’un K-espace vectoriel E vérifiant f ◦ g = Id. Montrer que Ker(f ) =
Ker(g ◦ f ), Im(g) = Im(g ◦ f ) puis que Ker(f ) et Im(g) sont supplémentaires.

Problem 3.
Soient f et g deux endomorphismes d’un espace vectoriel E sur R ou C vérifiant f ◦ g = Id.

(a) Montrer que Ker(g ◦ f ) = Ker(f ) et Im(g ◦ f ) = Im(g).


(b) Montrer
E = Ker(f ) ⊕ Im(g)

(c) Dans quel cas peut-on conclure g = f −1 ?


(d) Calculer (g ◦ f ) ◦ (g ◦ f ) et caractériser g ◦ f

Problem 4.
Soient f, g ∈ L(E) tels que
g◦f ◦g =g et f ◦ g ◦ f = f.

(a) Montrer que les espaces Im(f ) et Ker(g) sont supplémentaires dans E.
(b) Justifier que f (Im(g)) = Im(f ).

Problem 5.
Soient f, g ∈ L(E) tels que
g◦f ◦g =f et f ◦g◦f =g

(a) Montrer que Ker(f ) = Ker(g) et Im(f ) = Im(g). On pose

F = Ker(f ) = Ker(g) et G = Im(f ) = Im(g)

1
Algebra Linear Transformations TD 2
(b) Montrer que
E =F ⊕G

Problem 6.
Soit E un espace vectoriel sur K et soit f un endomorphisme de E. Etablir l’équivalence des assertions
suivantes:

(a) Ker(f ) ∩ Im(f ) = {0E }.


(b) Ker(f ◦ f ) = K er(f ).

Problem 7.
Soit E un espace vectoriel sur K et soient f et g des endomorphisme de E. Montrer que

f [Ker(g ◦ f )] = Im(f ) ∩ Ker(g)

Problem 8.
Soit E un espace vectoriel sur K et soient f, g et h des endomorphisme de E tels que

f ◦ g = h, g ◦ h = f, h ◦ f = g.

Montrer que
Ker(f ) = Ker(g) = Ker(h) et Im(f ) = Im(g) = Im(h)

Problem 9.
Soient E et F des espaces vectoriels sur K. Soient f une application linéaire de E vers F et g une application
linéaire de F vers E, telles que
f ◦ g ◦ f = f et g ◦ f ◦ g = g.
Montrer que
E = Im(g) ⊕ K Er(f ) et F = Im(f ) ⊕ Ker(g)

Problem 10.
Soit E un espace vectoriel sur K et soit f un endomorphisme de E. On pose f 0 = IdE et pour tout entier
k ∈ N∗
fk = f ◦ f ◦ . . . ◦ f .
| {z }
k fois
n
De plus, pour tout polynôme P (X) = an X + . . . + a1 X + a0 de K[X], on pose

P (f ) = an f n + . . . + a1 f + a0 IdE

On suppose qu’il existe un polynôme P (X) ∈ K[X] tel que

P (0) = 0 et P ′ (0) ̸= 0

2
Algebra Linear Transformations TD 2

un P (X) désigne le polynôme dérive de P (X). Montrer que si P (f ) = 0L(E) , alors:

E = Ker(f ) ⊕ Im(f )

Problem 11.
Let E be a finite dimenional vector space with n = dim(E). Let f, g ∈ L(E) such that

f + g = IdE and rank(f ) + rank(g) ⩽ n

a) Show that E = Im(f ) ⊕ Im(g).

b) Deduce that f and g are projectors in E.

Problem 12.
Let E and F be two finite dimensional vector spaces. Let (f, f ′ ) ∈ (L(E, F ))2 . Show that

|rank(f ) − rank (f ′ )| ⩽ rank (f + f ′ ) ⩽ rank(f ) + rank (f ′ )

Problem 13.
Let f be endomorphism in R3 nipotent of order 3, that is, f 3 = 0 and f 2 =
̸ 0. Show that

Ker f 2 = Im(f ), Im f 2 = Ker(f ), rank(f ) = 2, rank f 2 = 1


  

Problem 14.
Let E, F and G be three vector spaces and let f ∈ L(E, F ), g ∈ L(F, G). Show that the following properties
are equivalents:

a) g ◦ f is an isomorphism from E to G
b) f is injective, g is surjective and F = Ker(g) ⊕ Im(f )

Problem 15.
Let E be a finite dimensional vector space and let f ∈ L(E) such that

f 2 − 3f + 2Id = 0

a) Show that f is invertible and express its inverse in terms of f .


b) Show that E = Ker(f − Id) ⊕ Ker(f − 2Id).

Problem 16.
Let f, g, h ∈ L(E) such that f ◦ g = h, g ◦ h = f and h ◦ f = g.

3
Algebra Linear Transformations TD 2
a) Show that f, g and h have the same kernel and image.
b) Verify that f 5 = f

c) Deduce that E = Ker(f ) ⊕ Im(f ).

Problem 17.
Let E be a vector space and let f, g be two endomorphism in E such that f ◦ g = Id.

a) Show that Ker(g ◦ f ) = Ker(f ) and Im(g ◦ f ) = Im(g)

b) Show that E = Ker(f ) ⊕ Im(g)


c) In what case that we can conclude g = f −1 ?
d) Calculate (g ◦ f ) ◦ (g ◦ f ) and then deduce the type of transformation g ◦ f

Problem 18.
Let p and q be two projectors of vector space E

a) Prove that p + q is a projector if and only if p ◦ q = p ◦ q = 0


b) If p + q is a projector, show that Im(p + q) = Im(p) ⊕ Im(q)
c) If p + q is a projector, show that Ker(p + q) = Ker(p) ∩ Ker(q)

Vous aimerez peut-être aussi